Approach to Emergent Neurotrauma-related Neurosurgical Procedures in Patients with Hepatic Disease - Mendoza-Avendaño, María; Ramírez-Carvajal, Ana; Barreto-Herrera, Iván; Muñoz-Báez, Karen; Ramos-Villegas, Yancarlos; Shrivastava, Adesh; Janjua, Tariq; Moscote-Salazar, Luis Rafael; Agrawal, Amit (Indian Journal of Neurotrauma, 2021)
Liver diseases constitute a group of pathologies of extraordinary importance, because of the large number of patients who suffer from these as well as the consequences that they can have on these individuals if they undergo any surgical procedure. Therefore, these patients have greater risk of suffering unfavorable outcomes than a healthy person undergoing emergency neurosurgical procedures (ENP) for neurotrauma. For this reason, there is a need to classify these patients according to their surgical risk based on risk factors secondary to the concurrent hepatic derangements. Among the possible tools that allow us to stage patients with liver disease are the Child–Turcotte–Pugh (CTP) and model for end-stage liver disease (MELD) scales, which have proven utility in effectively predicting the outcomes, including morbidity and mortality in hepatic disease patients who are undergoing surgery. They also help to predict the risk of complications such as intracranial hemorrhage secondary to coagulopathy due to hepatic derangement.
Keywords: hepatopathies; liver disease; neurosurgery